Analysis of The Frame Design of Cracker Sheet Printing and Cutting Machine Using Finite Element Method Simulation - Effendi, Riki; Pratama, Rikardo; Qadri, Munzir; Yunus Nasution, Ahmad (DINAMIS, 2024)
The food industry continues to evolve and faces challenges in enhancing production efficiency. One product that has garnered significant attention is crackers, which have high global demand. Manual processes involved in printing and cutting cracker sheets result in time and labor wastage, leading to production limitations and reducing the industry's competitiveness. Therefore, this research aims to analyze the design framework of a cracker sheet printing and cutting machine using finite element method simulation. The research methodology involves 3D modeling of the machine framework, selection of appropriate materials, and configuration of finite element method simulation to understand the structural behavior of the machine. The research findings identify critical areas requiring design improvements to enhance machine reliability and operational efficiency. By leveraging automatic cutting technology, this research is expected to enhance cracker production efficiency, reduce production costs, and improve the competitiveness of local food industries in the global market. Using cracker sheet printing and cutting machines, cracker production can be significantly enhanced compared to manual processes. These findings make a significant contribution to improving production efficiency and the competitiveness of the food industry.